CONTRIBUTION OF INCOME FROM TOURISM SECTORS TO FISHERMAN FAMILIES INCOME IN MALANG RAPAT VILLAGE, BINTAN REGENCY, RIAU ISLAND PROVINCE - Sianipar, Sapta Mart Winda; Darwis, Darwis; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Researchon contribution of income from tourism sectors to fisherman families income was conducted in May 2018 in the Malang Rapat Village of GunungKijang District, Bintan Regency, Riau Island Province. This study was aimed to calculate the income of fishermen households from fishing efforts, calculate the income of fishermen households from businesses related to the tourism sector, and analyze the contribution of income from businesses related to the tourism sector to the income of fishermen households. The method used in this study is the survey method which is analyzed using the formula of the contribution of the marine tourism sector income and the number of respondents in this study is 21 respondents. From the results of the research analysis, it was found that fishermen were divided into two types based on fishing gear, namely nylon net fishermen and fishermen bubu. The average income earned by nylon net fishermen in fishing business is around IDR. 65,538,233 per year with monthly income of around IDR. 5,461,519, while the income earned by fishermen in bubu is around IDR. 17,401,544 per year with monthly income of around IDR. 1,450,129. The income received by fishing households from the tourism sector ranges from IDR. 500,000 to IDR. 3,100. 000 per month. The value of the contribution of fishermen's household income from the tourism sector is 62,54% and is classified as a high contribution.Keywords: contribution, income, tourism